2019 Global report on food crises: Joint analysis for better decisions: Update - Food Security Information Network (Food and Agriculture Organization of the United Nations, 2019)
The Global Report on Food Crises (GRFC), released annually, provides a consensus-based view of the numbers of people in urgent need of assistance for food, nutrition and livelihood support at the worst point during the previous year. For the last three years the report has indicated that despite the efforts of national governments and humanitarian actors, the number has not fallen below 100 million people globally, with conflict and insecurity, climate-related issues and economic shocks being the primary drivers of food insecurity. Humanitarian agencies, governments and other stakeholders need to be able to better understand and respond effectively and promptly to food crises with immediate life-saving assistance and livelihood support as well as preventive action, including resilience-building programmes and longer-term development policies. To do so they need the most recent consensual evidence-based analysis. They need to know the severity of the situation in terms of numbers of acutely food-insecure people and whether the situation is improving, deteriorating or stable, and why so. The GRFC partners are responding to that need to support timely responses and preventive actions to food crises by issuing this analytical mid-year update of the GRFC 2019 with the use of relevant information made available by September 2019.